Career Development of Medium Officers in Territorial Commands in the Reform Era Abdul Rahman State Administration at Stisospol Waskita Dharma Malang - Rahman, Abdul (Budapest International Research and Critics University, 2022)
The role of the TNI has received quite a sharp spotlight, the demand for the abolition of dual function is the main issue due to too strong a position so that the position of community participation becomes very weak. As in Law Number 32 of 2004 concerning Governance, it is stated that the decentralization policy limits the fields of foreign policy, monetary and fiscal, judiciary, defense and security, and religion are sectors that have not experienced decentralization. To support the main tasks of the Army, which has a vision of a TNI that is professional, transparent, honest and fair and accountable based on good morals in the development of TNI AD personnel. This vision is very noble, so it is hoped that it can be guided and implemented in personnel development activities by all ranks of TNI AD personnel. In order to provide an understanding of the development of TNI AD personnel to all Army Soldiers, the political and legal reforms that are currently taking place in Indonesia, the TNI is also making improvements. The most important decisions that have been taken include the neutralization of the TNI from practical politics, and the abandonment of the wealth doctrine. At the same time, the legal aspect of carrying out its functions and roles is also very important, so that whatever the TNI does must be measured by accountability measures. So, if we want to examine the repositioning of ABRI/TNI, the first thing to mention is the change in authority that is increasingly limited and measurable. TNI cannot be separated from the continuity process; what is now, cannot be separated from the past. The TNI must always evaluate, make changes for the better, and for that it does not only depend on the TNI itself, because politicians also have to understand and contribute, apart from continuing to improve themselves as well.